Medium-sized Universities Connect to Their Libraries: Links on University Home Pages and User Group Pages - Pamela Harpel-Burk (Information Technology and Libraries, 2006)
From major tasks—such as recruitment of new students and staff—to the more mundane but equally important tasks—such as providing directions to campus—college and university Web sites perform a wide range of tasks for a varied assortment of users. Overlapping functions and user needs meld to create the need for a Web site with three major functions: promotion and marketing, access to online services, and providing a means of communication between individuals and groups. In turn, college and university Web sites that provide links to their library home page can be valuable assets for recruitment, public relations, and for helping users locate online services.